2020
DOI: 10.1002/aid2.13182
|View full text |Cite
|
Sign up to set email alerts
|

Postembolization fever after transarterial chemoembolization is a sign of unfavorable therapeutic response in hepatocellular carcinoma patients

Abstract: Transarterial chemoembolization (TACE) is the standard of care for intermediate‐stage hepatocellular carcinoma (HCC) patients. The postembolization fever (PEF) is observed in 20% to 73% patients. This study aims to investigate the predictive factors of PEF and its impact on therapeutic response. From 2010 to 2015, a total of 525 HCC treatment naïve patients treated by TACE were recruited. Age, gender, etiologies of HCC, cirrhosis, tumor status, and pretherapy liver biochemistry were compared between patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…SNMC has been shown to have effects other than anti‐hepatotoxicity and anti‐inflammation, and this may reduce these subjective complaints 4 . Additionally, a study in Taiwan showed that post‐embolization fever after TACE is a sign of unfavorable therapeutic response in patients with HCC 13 . However, the tumor response to TACE was beyond our study design.…”
Section: Discussionmentioning
confidence: 94%
“…SNMC has been shown to have effects other than anti‐hepatotoxicity and anti‐inflammation, and this may reduce these subjective complaints 4 . Additionally, a study in Taiwan showed that post‐embolization fever after TACE is a sign of unfavorable therapeutic response in patients with HCC 13 . However, the tumor response to TACE was beyond our study design.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study reported that macrovascular invasion is a predictor of early HCC recurrence, whereas diabetes mellitus is a predictor of late HCC recurrence in patients with CR. (11) These parameters were not analyzed in the present study, but should also be considered as a tailored post-TACE follow-up strategy.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…The impact of the initial tumor size on the time to relapse, maximum diameter reduction, and recurrence rates need to be explored. (11) This information is essential for patients undergoing neoadjuvant therapy, to better indicate DEB-TACE therapy in the pre-transplantation scenario based on real perspectives regarding HCC diameter reduction for downstaging and to establish better standards of radiological follow-up based on the average tumor recurrence time for patients undergoing bridge therapy. This could also potentially decrease the rate of exclusion from the liver transplantation waiting list (dropouts).…”
Section: ❚ Introductionmentioning
confidence: 99%
“…These findings were consistent with previous research [ 9 , 12 ]. Except these, treatment related factors have also shown to be closely correlated with the prognosis after TACE treatment, including number of TACE sessions [ 55 ], and response to TACE [ 56 ]. Furthermore, TACE may combine with other treatment options like tyrosine kinase inhibitors, radiofrequency ablation or immunotherapy, which also exerts significant effects on the treatment outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%